The Effect of Topic Familiarity on Improving EFL Saudi Female Students` Reading Comprehension - Alrowaithy, Afaf Ayed (Journal of Educational and Psychological Sciences, 2021)
This study investigates the effect of topic familiarity on the reading comprehension performance of Saudi EFL students. Forty EFL Saudi female students on second year high school performed two tests: familiar versus unfamiliar topics in a multiple-choice format reading comprehension test each have 10 points with four texts two familiar and two unfamiliar texts. Quantitative analysis was undertaken in this study as a T test applied for both paired samples. The descriptive statistics shows that the arithmetic averages the students` performance on familiar topic larger than the arithmetic average on unfamiliar topic. The analytical statistics that identified the differences between both arithmetic averages shows that the differences among the students' performance on familiar and unfamiliar topic were large and have statistical significance in favor of their performance on familiar topic. Further replication of similar studies is necessary to determine the potential impact of topic familiarity on reading instructions and assessment design.
Keywords: familiar topic; texts; unfamiliar topic; reading comprehension; English curriculum